Correlation between 2,4-D herbicide residues and soil attributes in southern of Brazil (Revista Ciência Agronômica, 2023)
The 2,4-D herbicide is widely used in Brazilian and global agriculture to control weeds. It is potentially toxic tomankind, and one of the herbicides final destinations is the soil. The aim of the study was to determine the spatial correlationof 2,4-D herbicide in soil attributes after 12 months of application. The experiment was conducted in an agricultural area of5.04 ha in the municipality of Nova Santa Rosa/PR, in 2011 and 2012. Two soil samples collections were performed: collection1 (09/03/2011) and collection 2 (08/25/2012), both of which were made 12 months after 2,4-D application. The herbicide wasapplied in a single dose of 1.5 L ha-1 in 09/2010 and in two doses in 09/2011 (1.0 L ha-1or 1.5 L ha-1 2,4-D). The correlationbetween soil attributes and 2,4-D was determined with the use of a spatial correlation matrix. The 2,4-D soil residues variedwidely from one location to another in the same area, with points of no detection of the active ingredient. It was not possibleto detect differences between 1.0 L ha-1 and 1.5 L ha-1 2,4-D treatments. Several factors may have interfered in the herbicideresidues in the soil, including: climate, product characteristics, physical and chemical soil characteristics, soil management,among others. The spatial correlation of the soil attributes and 2,4-D residues in the soil proved to be an important tool to verifyone parameter interference over another.